Estimating nitrogen mineralizalion in a "cerrado" dark-red latosol by laboratory incubalion, and lhe effect of soil sample disturbance. - Klausner, Stuart D.; Suhet, Allert Rosa; Duxbury, John M. (Pesquisa Agropecuaria Brasileira, 2014)
Four dark-red latosols (Haplustox) were sampled at or near the "Centro de Pesquisa Agropecuária dos Cerrados - CPAC" - (Cerrados Agricultural Research Center), in Planaltina, DF, Brazil. A laboratory soil incubation study, at 35 ºC and 0.25 bar water tension, was conducted to evaluate the effect of soil disturbance on N mineralization and to determine the suitability of an incubation procedure for estimating N mineralization in the field. Mineralization rates ranged from 1.2 to 8.8kg N ha-1 wk-1 over a twelve-week period. The data suggested that as long as there is some degree of soil aggregation, soil disturbance had no effect on N mineralization. The amount of N mineralized during the incubation period in the laboratory showed a low correlation with the N mineralization in the field.